Toward regional science and technology development in CARICOM territories and Suriname : new and renewable energy, agro-industry and food technology, non-metallic minerals - Minott, Dennis A. (Enerplan Ltd KingstonJM, 1982)
Examines status and level of science and technology activities for development in CARICOM states and Suriname with special attention to new and renewable energy; agro-industry and food technology and non-metallic minerals and building materials. Report concludes with 9 regional project proposals for implementation within the next five years ending in 1988.